The Effect Of Generative Learning Model Based On Cognitive Conflict On Students’ Critical Thinking Skills to Global Warming Material - Rismayanti, Ellya (PILLAR OF PHYSICS EDUCATION, 2025)
This research was conducted to investigate the effect of a generative learning model based on cognitive conflict on students’ critical thinking skills in the topic of global warming. The foundational problem for this research is the inadequate level of critical thinking demonstrated by students in learning environments. The study utilized a quasi-experimental methodology with a pretest-posttest design involving a control group. Through purposive sampling, students from class XE 2 were assigned to the experimental group, while students from class XE 4 formed the control group. Data were gathered using a set of essay questions that were formulated based on indicators of critical thinking. The instrument's accuracy and consistency were confirmed through prior validity and reliability tests, and the final data were derived from the test results of both student groups. The non-parametric Mann-Whitney test was selected for data analysis as the data did not exhibit a normal distribution. The findings revealed that the average posttest score of the experimental group (61.03) was higher than that of the control group (49.39). Based on the statistical calculation results, the zcount  value was 3.44 and the Z table value was 1.96 with a significance level of 5%. Because the zcount Z valuewas greater than the Z table (3.44 > 1.96), Ho wasrejected and H1 was accepted. These results indicate that the cognitive conflict-based generative learning model positively influences the improvement of students’ critical thinking skills.